Pengaruh Pertumbuhan Ekonomi, Tingkat Pengangguran Dan Jumlah Penduduk Terhadap Kemiskinan Di Kabupaten Manokwari - Aprilia P.S. Faidiban; Amran T. Naukoko; Krest D Tolosang (PT. Hasba Edukasi Mandiri, 2025)
Poverty remains a multidimensional challenge influenced by economic growth, unemployment, and population growth dynamics. While numerous studies have examined the relationship between economic growth and poverty, research that integrates unemployment and population growth variables at the district level, particularly in Eastern Indonesia, remains limited. This study aims to analyze the impact of economic growth, unemployment, and population growth on poverty levels in Manokwari Regency from 2009 to 2023. Utilizing time-series secondary data from 2009 to 2023 and multiple linear regression analysis, the findings indicate that economic growth and unemployment significantly reduce poverty, whereas population growth increases poverty levels. Collectively, these three variables demonstrate a significant influence on poverty dynamics. This study underscores the importance of district-level policies that not only prioritize economic growth but also emphasize job creation and human capital development as sustainable strategies for poverty alleviation.